2017
DOI: 10.1016/j.cplett.2017.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Microbial reduction of graphene oxide by Azotobacter chroococcum

Abstract: We report an eco-friendly route for the reduction of graphene oxide (GO) by Azotobacter chroococcum at room temperature. Examinations using X-ray photoelectron spectroscopy, X-ray diffraction, and transmission electron microscopy indicate the formation of reduced graphene oxide (rGO) with a low degree of agglomeration. Quantitative analyses of electron diffraction data show that the produced rGO consists of single-layer sheets with a random stacking. It is suggested that the GO was reduced directly by the nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(26 citation statements)
references
References 42 publications
(55 reference statements)
0
26
0
Order By: Relevance
“…The high-resolution spectrum of C 1s ( Figure 3B ) could be deconvoluted into three peaks at 284.1 (C-C/C=C), 285.6 (C-O/C=N) and 287.6 eV (C=O). 35 , 36 In the high-resolution O 1s spectrum ( Figure 3C ), two peaks at 530.5 and 531.9 eV were attributed to the presence of O-H and O-C=O bonds, respectively. 37 , 38 Two peaks at 399.3 and 400.3 eV were in the high-resolution N 1s spectrum ( Figure 3D ), revealing the existence of pyridinic N and pyrrolic N. 39 The synthesis yield of RSFC-CDs was 3.14 ± 0.2%.…”
Section: Resultsmentioning
confidence: 99%
“…The high-resolution spectrum of C 1s ( Figure 3B ) could be deconvoluted into three peaks at 284.1 (C-C/C=C), 285.6 (C-O/C=N) and 287.6 eV (C=O). 35 , 36 In the high-resolution O 1s spectrum ( Figure 3C ), two peaks at 530.5 and 531.9 eV were attributed to the presence of O-H and O-C=O bonds, respectively. 37 , 38 Two peaks at 399.3 and 400.3 eV were in the high-resolution N 1s spectrum ( Figure 3D ), revealing the existence of pyridinic N and pyrrolic N. 39 The synthesis yield of RSFC-CDs was 3.14 ± 0.2%.…”
Section: Resultsmentioning
confidence: 99%
“…were then breakdown by anaerobic bacteria and eventually converted to methane by methanogens (Sun et al, 2014;Sun et al, 2015;Tian et al, 2017). Previous investigations have reported that nano-graphene and Fe 3 O 4 nanoparticles induced positive effects on the methane yield (Li et al, 2015;Tian et al, 2017).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…For example, thermal treatment of the NGO-WAS mixture could be applied to remove carboxyl groups of NGO to release the absorbed SCOD from NGO (McAllister et al, 2007;Schniepp et al, 2006;Zhu et al, 2017), which would potentially facilitate the carbon transformation and methane production from WAS. Also, chemical reduction of hydrazine vapor could also be tried transfer NGO to the form of graphene (Gao et al, 2010;Park et al, 2012;Ren et al, 2011), which has been demonstrated to be able to facilitate methane production in anaerobic digestion (Tian et al, 2017). In addition, microbial reduction could serve as an environmental-friendly method to replace chemical and thermal reduction of NGO.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the C/O atomic ratio and electrical conductivity obtained are inferior to the chemical methods [ 42 , 52 ]. Microbes such as Shewanella [ 132 ] , E. coli [ 133 ] , yeast [ 134 ] , and Azotobacter chroococcum [ 135 ] can also reduce GO in the forms of dispersion or film. Though such biological agents are attractive with low-negative environmental impact, they are limited in terms of the need for sensitive culture procedure and prolonged reaction time [ 49 ].…”
Section: Go/rgo: Properties Reduction Methods and Characterizatimentioning
confidence: 99%